2020
DOI: 10.1002/ejoc.202000876
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Application of Vibrational Circular Dichroism Spectroscopy for the Characterization of Asymmetric Catalysts

Abstract: In this Minireview, we summarize our recent efforts to use vibrational circular dichroism (VCD) spectroscopy, the chiroptical version of IR spectroscopy, for the characterization of conformational preferences of asymmetric catalysts and complexes, formed upon the respective interactions or reactions of catalysts with substrates. After giving a brief overview of the general aspects of the technique, we showcase how VCD spectra of a chiral ion-pairing catalyst could be used to confirm a conformational shifting m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 80 publications
0
33
0
2
Order By: Relevance
“…The information about the structure and behavior of both acids provided by vibrational spectroscopies can be extended by their chiral variants: vibrational circular dichroism (VCD) and Raman optical activity (ROA). , VCD and ROA detect small differences in, respectively, absorption and scattering of left- and right-circularly polarized light by chiral molecules. Both methods have proven their efficiency in providing unique fingerprint information about conformational behavior, higher-order structural arrangement, intermolecular interactions, and solvation that cannot be obtained from the corresponding unpolarized methods. Nevertheless, works focusing on chiroptical features of carboxylic acids are rather rare. Merten et al studied the effect of solvation on conformation, hydrogen bonding, and dimerization propensities of several chiral, mostly aromatic, carboxylic acids using a combination of experimental and theoretical VCD. Furthermore, there are two publications on ROA of tartaric acid (refs and ) but no reports of either VCD or ROA of malic acid and only few of lactic acid, , including one structural study of polylactic acid .…”
Section: Introductionmentioning
confidence: 99%
“…The information about the structure and behavior of both acids provided by vibrational spectroscopies can be extended by their chiral variants: vibrational circular dichroism (VCD) and Raman optical activity (ROA). , VCD and ROA detect small differences in, respectively, absorption and scattering of left- and right-circularly polarized light by chiral molecules. Both methods have proven their efficiency in providing unique fingerprint information about conformational behavior, higher-order structural arrangement, intermolecular interactions, and solvation that cannot be obtained from the corresponding unpolarized methods. Nevertheless, works focusing on chiroptical features of carboxylic acids are rather rare. Merten et al studied the effect of solvation on conformation, hydrogen bonding, and dimerization propensities of several chiral, mostly aromatic, carboxylic acids using a combination of experimental and theoretical VCD. Furthermore, there are two publications on ROA of tartaric acid (refs and ) but no reports of either VCD or ROA of malic acid and only few of lactic acid, , including one structural study of polylactic acid .…”
Section: Introductionmentioning
confidence: 99%
“…3 As a chiroptical version of infrared (IR) spectroscopy, VCD spectroscopic signatures can be affected by intermolecular interactions. While this sensitivity can be exploited to characterize interactions in asymmetric catalysis [8][9][10][11][12][13] and biomolecules, 14,15 solute-solvent hydrogen bonding may cause unforeseen effects on the VCD spectra. 16,17 During an AC assignment, such solvent-influences are often discovered by accident; that means when the spectra calculations on the isolated target molecule do not match with the experimental signatures.…”
Section: Introductionmentioning
confidence: 99%
“…Crystallography and NMR spectroscopy are the most frequently used methods to characterize anion binding to thioureas. In the context of our work on asymmetric organocatalysts, 10 we recently used vibrational circular dichroism (VCD) spectroscopy, the chiroptical version of infrared spectroscopy, to gain more detailed insights into the solution phase conformational preferences of chiral thioureas and their hydrogen bonded complexes. [11][12][13] These and other studies demonstrated that VCD spectroscopy is very sensitive to interaction induced conformational changes.…”
Section: Introductionmentioning
confidence: 99%